Association between the occurrence of adenomyosis and the clinical outcomes of vaginal repair of cesarean section scar defects: an observational study - Huihui Chen; Wenjing Wang; Husheng Wang; Xipeng Wang (BMC, 2022)
Abstract Background To examine the correlation between the occurrence of adenomyosis and the outcome of vaginal repair of cesarean section scar defects (CSDs). Methods A total of 278 women with CSD were enrolled in this retrospective observational cohort study at the Shanghai First Maternity & Infant Hospital between January 2013 and August 2017. Patients were divided into two groups according to preoperative magnetic resonance imaging (MRI) findings: the adenomyosis group and the non-adenomyosis group. They all underwent vaginal excision and suturing of CSDs and were required to undergo examinations 3 and 6 months after surgery. Preoperative and postoperative clinical information was collected. Optimal healing was defined as a duration of menstruation of no more than 7 days and a thickness of the residual myometrium (TRM) of no less than 5.8 mm after vaginal repair. Results Before vaginal repair, for patients in the adenomyosis group, the mean duration of menstruation was longer and TRM was significantly thinner than those in patients in the non-adenomyosis group (p < 0.05). The TRM and duration of menstruation 3 and 6 months after surgery were significantly improved in both groups (p < 0.05). There were more patients with optimal healing in the non-adenomyosis group than in the adenomyosis group (44.7% vs. 30.0%; p < 0.05). Furthermore, 59.3% (32/54) of the women tried to conceive after vaginal repair. The pregnancy rates of women with and without adenomyosis were 66.7% (8/12) and 61.9% (26/42), respectively. The duration of menstruation decreased significantly from 13.4 ± 3.3 days before vaginal repair to 7.6 ± 2.3 days after vaginal repair in 25 patients (p < 0.001). The TRM increased significantly from 2.3 ± 0.8 mm before vaginal repair to 7.6 ± 2.9 mm after vaginal repair (p < 0.001). Conclusions Vaginal repair reduced postmenstrual spotting and may have improved fertility in patients with CSDs. Patients with adenomyosis are more likely to have suboptimal menstruation and suboptimal healing of CSDs. Adenomyosis might be an adverse factor in the repair of uterine incisions.